Consumer acceptance of urban drone delivery: the role of perceived anthropomorphic characteristics - Li, Xue (2024)
With the growth of online retailing, drone delivery has emerged as a potential solution for efficient last-mile delivery. As consumer acceptance is a key prerequisite for the wide application of drones, this research aims to understand the role of anthropomorphic characteristics in consumer acceptance of drone delivery services. The theoretical explanatory model is anchored on the theory of planned behaviour and anthropomorphism theory. A total of 450 responses were collected from Singapore. It was found that perceived anthropomorphic characteristics of delivery drones and interaction quality with delivery drones positively and significantly impact consumers' behavioural intention toward drone delivery. In addition, the findings suggested that perceived anthropomorphic characteristics of delivery drones positively and indirectly influence consumers' behavioural intentions through subjective norms, perceived behavioural control, and attitudes. This study contributes to behavioural research by introducing anthropomorphism to explain consumers' intentions toward drone delivery. The results provide practical implications for drone manufacturers, service providers, and regulators for fostering consumers' acceptance of drones via product design, marketing, and regulations.